Quality characteristics and microbial status of beef smoked with different plant materials (2014)
A study was conducted to evaluate the effect of smoking beef using different plant materials as sources of smoke in Zaria, Kaduna State. The effect of smoke from four plant materials (Acacia raddiana, Eucalyptus camaldutensis, Azadirachta indica and Cocos nucifera) on organoleptic, microbial and physicochemical properties of smoked beef was evaluated. There was no significant (P>0.05) difference among the sources of fuel wood tested on the overall acceptability of smoked meat. The organoleptic scores (1.40-3.50) were lowest for beef smoked with in C. nucifera and highest for beef smoked with A. raddiana (standard check). The pH values were within the accepted limit (5.5-6.5). Percentage thermal shortening was highest (7.00%) in beef smoked with A. raddiana. Total viable counts/Aerobic plate count, coli-form counts were all within safe limits (i.e. <1/2 million/g). It was concluded that Eucalyptus camaldutensis (Turare), Azadirachta indica (Neem) and Cocos nucifera (coconut husk) are good sources of fuel wood and can be used as an alternative to Acacia raddiana for smoking beef.